Drug Use among a Sample of Federal Drug Crime Defendants: Implications for the Gateway Effect Hypothesis - David Reitzel, John; Scarbrough, Sarah Huggins (International Journal of Criminology and Sociology, 2017)
This study investigated the association between marijuana first before other drugs and alcohol and later hard drug among a convenience sample of federal drug crime defendants from one federal court in the Mid-Atlantic region of the United States. Results from two binomial logistic regression models revealed statistically significant associations between first use of marijuana and regular drug use and hard drug use, respectively. Findings suggests a gateway effect for marijuana within this sample.